Atypical Spitz tumours: an epidemiological, clinical and dermoscopic multicentre study with 16 years of follow‐up. (6th June 2022) - De Giorgi, Vincenzo; Venturi, Federico; Silvestri, Flavia; Trane, Luciana; Savarese, Imma; Scarfì, Federica; Cencetti, Francesca; Pecenco, Silvia; Tramontana, Marta; Maio, Vincenza; Zuccaro, Biancamaria; Colombo, Jacopo; et al.
Summary: Background: Atypical Spitz tumours (ASTs) are regarded as an intermediate category distinguished from prototypical Spitz naevus by presenting one or more atypical features and often by an uncertain malignant potential. Clinical and dermoscopic features may play a relevant role in the diagnostic approach. Aim: To evaluate the clinical and dermoscopic features of ASTs, and their evolution over time. Methods: This was a descriptive, multicentre study of the clinical and dermoscopic characteristics of ASTs. Data on clinical and dermoscopic characteristics, histopathology, local extension, therapy and follow‐up, lymph node staging, complete lymph node dissection, and outcome were collected from the databases of four Italian Dermatology Units for the period 2004–2021. Results: The study population consisted of 99 patients (62 female, 37 male) with a histologically confirmed diagnosis of AST, including age at presentation ranged from 2 to 70 years (mean 28.1 years, median 24 years). Of the 99 patients, 29 (29.3%) underwent sentinel lymph node biopsy, which showed evidence of micrometastases in three cases (10.3%); all three patients underwent complete lymph node dissection with no evidence of further metastasis. Considering the whole study population, the clinical outcome was excellent, as all of the patients have no evidence of recurrence or distant metastasis. The follow‐up period ranged from 6 to 216 months (mean 81.6 months, median 78 months). In addition, we collected data on the clinical and dermoscopic features of 26 lesions. The most frequent dermoscopic pattern observed was the multicomponent pattern (34.6%), followed by homogeneous (26.9%) and nonspecific (23.2%). In 66.7% of amelanotic ASTs, we observed glomerular (coiled) vessels uniformly distributed within the entire lesion, without asymmetry. Conclusion: The results of our study with a long follow‐up show no recurrence or distant metastases, confirming the good clinical outcome, even in the case of sentinel lymph node positivity. From a diagnostic point of view, our series identified a typical dermoscopic picture for amelanotic ASTs, with a glomerular vascular pattern throughout the lesion in the absence of other dermoscopic parameters, making the correct diagnosis possible. Abstract : Our data, which reflect 16 years of follow‐up time in a cohort of 99 patients, show a favourable prognosis with no event of distant metastasis or recurrence, even in cases with positive sentinel lymph node biopsy. Dermoscopically, in amelanotic atypical Spitz tumours (ASTs), we observed glomerular vessels uniformly distributed within the entire lesion, without asymmetry. Our study shows a typical dermoscopic picture regarding amelanotic ASTs with a glomerular vascular pattern in the absence of other dermoscopic parameters, making a correct diagnosis possible.